PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAERAH KABUPATEN LABUHANBATU SELATAN - Muhammad Robiq Muhazir; Waldy Depuansyah Harahap; Muhammad Zul Indra; Norman Hadiyanto; Fakhrurrazi Salim (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
Problem of this study how influence of leadership on performance. How influence of organization culture on performance. How influence of job dicipline on performance. How influence leadership, organization culture and job dicipline on performance. The purpose of this study to determine and analyze the effect of leadership on performance. Determine and analyze the effect of organization culture on performance. Determine and analyze the effect of job dicipline on performance. Determine and analyze the effect of leadership, organization culture and job dicipline on performance. Sample in the study is 34 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate leadership variable has a positive and significant effect on performance. organization culture variable has a positive and significant effect on performance. job dicipline variable has a positive and significant effect on performance. Leadership, organization culture and job dicipline variable has a positive and significant effect on performance.